Redox effects and formation of gold nanoparticles for the nucleation of low thermal expansion phases from BaO/SrO/ZnO/SiO2 glasses. Issue 12 (7th February 2018) - Kracker, Michael; Thieme, Christian; Thieme, Katrin; Patzig, Christian; Berthold, Lutz; Höche, Thomas; Rüssel, Christian
Abstract : Glasses in the system BaO/SrO/ZnO/SiO2 containing 0.01 and 0.1 mol% gold were used to study the formation of gold nanoparticles with the aim to use them as nucleation agents. Abstract : Glasses in the system BaO/SrO/ZnO/SiO2 containing 0.01 and 0.1 mol% gold were used to study the formation of gold nanoparticles with the aim to use them as nucleation agents. In order to promote gold clustering, the glasses were additionally doped with 0.5 mol% Sb2 O3 . Depending on the heat treatment schedule, Au particle sizes were in the range from 6 to above 50 nm. In contrast to many other gold ruby glass systems, the clustering is completely prevented by the absence of antimony; then the glasses remain colorless. Surprisingly, at higher temperatures, a re-dissolution of gold clusters was also observed, which now allows the formulation of a more comprehensive model concerning the redox and clustering behavior. This growth model is completed by the fact that a high gold concentration enables the stabilization of much smaller Au clusters. Mie theory with the aid of quantum confined size-dependent dielectric functions was successfully used to describe the optical behavior of the gold nanoparticles also for sizes below 10 nm. These results were confirmed using high resolution scanning transmission electron microscopy, including energy dispersive X-ray spectroscopy. It could also be shown that small gold particles up to a size of 50 nm are not effective as nucleating agents.